Urogynecological symptoms of the retroverted gravid uterus in the first half of the pregnancy: A retrospective cohort study of an underestimated, underdiagnosed and underreported issue: Lower urinary tract symptoms in patients with retroverted gravid uterus - Akturk, Erhan; Emeklioglu, Cagdas Nurettin; Ozer Caltek, Hale; Caltek, Necirvan Cagdas; Sahin, Fatih; Mihmanli, Veli (Journal of Surgery and Medicine, 2023)
Background/Aim: Urogynecological symptoms, including pelvic pain, lower backache, feeling of bearing down, frequency, nocturia, urgency, stress incontinence, and urge incontinence, are common during pregnancy. But little has been reported regarding possible changes in lower urogenital tract anatomy and its effects in pregnancy. Therefore, the subject of this study is whether the incidence of urogynecological symptoms is higher when the uterus is retroverted in pregnancy. Methods: We enrolled 1432 pregnant women examined before the 20th week of pregnancy between January 2018 and March 2022. Patients were allocated into two groups according to whether the uterus was retroverted (n=226 (15.7%)) or anteverted (n=1206 (84.3%)). These two groups were compared regarding pelvic pain, lower backache, the feeling of bearing down, frequency, nocturia, urgency, stress incontinence, and urge incontinence. Results: Retroverted gravid uterus was noted in 11.8% (n=41) of nulliparae and 17% (n=185) of multiparae (P=0.021), with an overall prevalence of 15.7%. Of 1432 patients, the overall prevalence for frequency, urgency, nocturia, urge incontinence, stress incontinence, lower backache, pelvic pain, and feeling of bearing down were 31%, 26.7%, 18.2%, 5.4%, 7.5%, 6.9%, 56.4% and 7.5%, respectively. Between both groups, there were differences in frequency, urgency, nocturia and lower back pain. There were two patients with incarcerated gravid uterus with urinary retention. Conclusion: Patients with a retroverted uterus are more likely to experience the symptoms of lower back pain, frequency, nocturia, and urgency in the first half of pregnancy.